UNIVERSITY JOURNALS: Consolidating institutional repositories in a digital, free, open access publication platform for all scholarly output - Woutersen-Windhouwer, Saskia; Méndez Rodríguez, Eva; Sondervan, Jeroen; Oort, Frans J. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
Funders increasingly mandate researchers to publish their scientific articles in open access and to retain their copyright. Universities all over the world have set up institutional repositories and use repositories for the preservation and dissemination of academic production of their institutions, including scientific articles, reports, datasets, and other research outputs. However, in general, authors do not find institutional repositories very attractive and accessible as an open access publication platform since repositories and open access are not part of the rewarding system. We expect that researchers are more likely to publish and deposit their scientific papers in a repository, once they have the appearance, recognition and dissemination of a scientific journal. That is why we took the initiative to set up a repository based journal ‘University Journals’ in which universities collaborate. The paper will explain the University Journals project and how the involved universities want to facilitate a valuable alternative publication platform that complies with Plan S principles and enables publication and dissemination of all research outcomes. By establishing University Journals as a publication platform, university libraries are instrumental (and crucial) in achieving the ambitions of Open Science, and universities gain control over the publication process.